PENGARUH KOMPOS DAN PUPUK ORGANIK CAIR PADA MEDIA TANAH BEKAS TAMBANG BATUBARA TERHADAP HASIL KEDELAI (Glycine max L.) - Mohamad Fadli; Candra Catur Nugroho; Aspianur Aspianur (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
This research was aim to know the effect using of composts and liquid organic fertilizer concentration toward the growth and yield of soybeans. This reasearch starts from April to July 2017, located Rempanga village, Kutai Kartanegara District.The study was arranged by randomized complete block design (RCBD) factorial 3 x 4 with 3 (three) replication. The first factor was compost doses with 3 levels i.e k0 = control (without using of compost), k1 = 15 t ha-1 (120 g plant-1), k2 = 30 t ha-1 (120 g plant-1). The second factor was the concentration of liquid organic fertilizer with 4 levels i.e. p0 = control (without using of liquid organic fertilizer), p1 = 20 mL L-1 water, p2 = 40 mL L-1 water, p1 = 60 mL L-1 water.The treatment of compost had no significant to the average of number of planted pods and the number of empty pods per plant but significantly different in weight of crop seeds with the highest weight obtained at the k2 treatment (17,167 g).The treatment of concentration of liquid organic fertilized had no significant effect on the average of number of empty pods and the number of empty pods per plant and weight of seeds. The highest weight obtained at the p3 treatment (15,222 g).The interaction between compost and a liquid organic fertilizer concentration had no significant to the average of number of planted pods, number of empty pods per plant and weight of seeds. The highest weights are obtained in the combination of k2p3 treatment (20,500 g).